Penyuluhan Penggunaan Antibiotik Rasional pada Wali Murid serta Perilaku Hidup Bersih dan Sehat pada Siswa - Putra, Dimas Setyadi; Firadusi, Dita Azmul; Nugraha, Rizki Lisya; Atmadani, Rizka Novia; Pertiwi, Ayu Kartika (Fisip UIN Sunan Gunung Djati Bandung, 2024)
The management of sources of infection becomes important once a pandemic begins, either through breaking the chain of disease spread or the use of drugs to reduce morbidity and mortality during the pandemic. However, the increasing changes in antibiotic use patterns during the COVID-19 pandemic can lead to new problems and disastrous impacts, such as antibiotic-resistant bacteria. In addition, the COVID-19 pandemic also has a major impact on the education sector; changes in everyone's attitude need to be made to maintain a healthy body, one of which is clean and healthy living behavior (PHBS). This education aims to educate parents about the rational use of antibiotics and improve knowledge and practice of PHBS in students in the pandemic era. The education was conducted using speech methods and brochure media in two elementary schools in Malang City. The results of this education showed an increase in audience understanding before and after the education, both regarding rational antibiotics and PHBS. Although the COVID-19 pandemic has passed, the results of this education can be useful as a reference in the future, showing that the role and collaboration between the government, academics, and communities are needed to facilitate activities that can increase people's knowledge or understanding that may motivate them in behavior or decision-making.